Effect of the annealing temperature on the photoconversion efficiency of heterostructured photoanode Bi2S3/ZnO nanorods in photoelectrochemical cells. (12th January 2021) - Al-Zahrani, Asla A.; Zainal, Zulkarnain; Talib, Zainal Abidin; Lim, Hong Ngee; Holi, Araa Mebdir; Bahrudin, Noor Nazihah
Bismuth (III) sulphide (Bi2 S3 ) sensitised zinc oxide (ZnO) nanorods have been synthesised using a successive ionic layer adsorption and reaction (SILAR) technique. The effect of annealing temperature on the performance of Bi2 S3 /ZnO NRAs/ITO as photoanode in photoelectrochemical cell has been investigated. The sensitisation of ZnO by Bi2 S3 was conducted with five different series of annealing temperatures from 100°C to 500°C. The UV-Vis clearly showed a significant shift in the absorbance edge toward the visible light spectrum with the increasing annealing temperature. The changes in the structure and morphology of the thin film before and after annealing have been studied using X-ray diffraction, Raman spectroscopy, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), high resolution transmission electron microscopy(HR-TEM) and energy dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). A significant enhancement in the photoelectrochemical performance was noticed for Bi2 S3 /ZnO NRAs upon the post-heat treatment at 300°C which exhibited an admirable photoconversion efficiency of 3.17% which was 13 times higher as compared with bare ZnO NRAs (0.25%). This improvement was ascribed to the enhanced surface area and improved visible light harvesting of the synthesised heterostructured photoanode.